Relatedness-dependent rapid development of brain activity in anterior temporal cortex during pair-association retrieval. (3rd August 2016) - Jimura, Koji; Hirose, Satoshi; Wada, Hiroyuki; Yoshizawa, Yasunori; Imai, Yoshio; Akahane, Masaaki; Machida, Toru; Shirouzu, Ichiro; Koike, Yasuharu; Konishi, Seiki
Highlights: It is known that long-term memory can be consolidated rapidly in one or two days. Activity in temporal neocortex during pair-association retrieval changed in one day. The activity change was more rapid when paired items were semantically related. Abstract: Functional MRI studies have revealed that the brain activity in the anterior temporal cortex during memory retrieval increases over months after memory encoding. Behavioral evidence has demonstrated that long-term memory can sometimes be consolidated more rapidly in one or two days. In the present functional MRI study, we manipulated the relatedness between paired faces to be retrieved in a pair-association task. The brain activity in the anterior temporal cortex during retrieval of paired associates increased rapidly in one day, as shown in previous studies. We found that the speed of the brain activity development was dependent on the level of semantic relatedness of paired faces. The results suggest that the semantic relatedness enhances the speed of formation of memory representation in the anterior temporal cortex.